Comparison of power outputs during time trialing and power outputs eliciting metabolic variables in cycle ergometry - Morris, D. M.; Shafer, R. S. (International Journal of Sport Nutrition and Exercise Metabolism, 2010)
The authors sought to compare power output at blood lactate threshold, maximal lactate steady state, and pH threshold with the average power output during a simulated 20-km time trial assessed during cycle ergometry. Participants (N = 13) were trained male and female cyclists and triathletes, all permanent residents at moderate altitude (1,525-2,225 m). Testing was performed at 1,525 or 1,860 m altitude. Power outputs were determined during a simulated 20-km time trial (PTT), at blood pH threshold (PpHT), at maximal lactate steady state (PMLSS), and at blood lactate threshold determined by 2 methods: the highest power output that did not result in consecutive and continued increases in blood lactate concentrations from exercising baseline (PLT) and the highest power output that did not result in consecutive and continued increases of =1 mmol/L in blood lactate concentrations from exercising baseline (PLT1). PLT, PLT1, and PMLSS were all significantly lower than PpHT (p < .05) and PTT (p < .05). No significant difference was observed between PpHT and PTT (p > .05). Significant correlations were observed between each of the metabolic variables, PLT, PLT1, PMLSS, and PpHT, compared with PTT (p < .05). The authors conclude that, of the 4 metabolic variables, only PpHT offered an accurate reflection of PTT.